SPATIAL CONFLICT, LOCAL POLITICS, AND THE PRESENCE OF ISLAMIC SOCIAL MOVEMENTS; GNPF Ulama in Medan - Faisal Riza; Hasyimsyah Nasution; Katimin Katimin (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Recently, cities in Indonesia are filled with the phenomenon of political movements from Islamic circles. They often carry out mobilization actions and street protests to negotiate the interests they carry which are considered as an attempt to color urban life. This article aims to discuss the presence of the Islamic social movement GNPF Ulama North Sumatra (hereinafter referred to as GNPF), to investigate the factors and key actors in the emergence of the movement, and the implications of the movement they played. This article is part of a field research conducted by observing and interviewing several movement activists. Then, the analysis in this article uses social movement theory. In this study, social movement theory is used in this case the political process and the structure of political opportunity. The findings in this article are that social movements are a reaction to the tightness of the socio-economic and political space. The emergence of Islamic social movements in contemporary Indonesian urban space is not only driven by old factors such as the influence of colonialism, moreover its emergence is driven by the process of modernization and urbanization of the city which results in spatial conflicts between business and religion. In addition, electoral political events at the local level also encourage the emergence of movements along with the existence of movement actors who also act as political actors. Here I argue that all the factors that have been mentioned have given rise to a broader aspect of studying how a movement arises